The development of positive education combined with online learning: Based on theories and practices - Lou, Jialing; Xu, Qinmei (Frontiers in Psychology, 2022)
In recent years, increasing attention has been paid to the all-around development and mental health of students in education. Positive education, a rapidly developing ramification of positive psychology, has proved beneficial to students' learning and wellbeing. Meanwhile, online learning has quickly gained popularity due to the impact of COVID-19. However, there have been few reports discussing the relationship between positive education and online learning by combining theories and practices. To explore the connection between positive education and online learning, we provide a literature review for studies, mostly between 2010s and 2022, of theories and practices for both positive education and online learning. Next, we establish one-to-one links between the relevant theories and practices of online learning to each domain in the PERMA model of positive education, a theoretical framework including Positive emotion(P), Engagement(E), Relationship(R), Meaning(M), and Accomplishment(A). We aim to explore how to promote the development of positive education by applying the theoretical and practical advantages of online learning to the PERMA framework of positive education. This study aims to enrich the research perspectives of positive education and provide a reference for future research.